Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1097/gox.0000000000001603
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Diagnosis and Treatment of Breast Lumps after Breast Augmentation with Autologous Fat Grafting

Abstract: Background:Breast augmentation with autologous fat has been performed in Japan for over 30 years. However, complications include breast lumps and oil cysts. Such breast lumps greatly reduce patient satisfaction, and are currently difficult to diagnose and treat for many cosmetic surgery clinics. This study aimed to elucidate the effectiveness of ultrasound diagnosis and treatment of patients with breast lumps after breast augmentation with autologous fat grafting.Methods:We used diagnostic and therapeutic ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The role of HRUS in examining the integrity and rotation of a breast implant has been of increasing interest [ 39 , 41 48 ]. Moreover, its role has been expanded to manage patients who are suspected of having BIA-ALCL as well as to examine a breast mass [ 49 , 50 ]. In this regard, plastic surgeons are required to make an HRUS-assisted approach to an implant-based augmentation mammaplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The role of HRUS in examining the integrity and rotation of a breast implant has been of increasing interest [ 39 , 41 48 ]. Moreover, its role has been expanded to manage patients who are suspected of having BIA-ALCL as well as to examine a breast mass [ 49 , 50 ]. In this regard, plastic surgeons are required to make an HRUS-assisted approach to an implant-based augmentation mammaplasty.…”
Section: Discussionmentioning
confidence: 99%
“…No distinct changes were observed in the BIRADS classification in 6 months postoperation. Masaaki et al analyzed the ultrasound results of 256 patients after fat grafting and found that 77% of the breasts had lumps located beneath the mammary glands, 17% beneath the skin, and 6% beneath the pectoralis major muscle (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…FIGURE 2 | (A)25-year-old female patient from the retropectoral group presented with involutional atrophy of the breasts. She received 300 mL lipoaspirates per breast, with 200 mL into the retropectoral space, 50 mL into the subcutaneous plane and 50 mL into the retromammary space.…”
mentioning
confidence: 99%
“…5.7 Oil cysts filled with necrotic material result in persistent inflammation, and calcification continues to develop over time, with these progressive changes persisting ( Mineda et al, 2014 ; Shida et al, 2017 ). Therefore, larger oil sacs should be suctioned under ultrasound guidance, taking care to ensure that all their contents are extracted ( Shida et al, 2017 ). If the suction is incomplete, the lump will persist and the patient will be dissatisfied.…”
Section: Clinical Avoidance Of Poor Extracellular Matrix Remodeling After Graftingmentioning
confidence: 99%